Analisis Pemetaan Mutu Pendidikan SMPN 3 Singorojo Kabupaten Kendal - Dewi Ratnawati; Titik Haryati (Melati Institute, 2024)
This study aims to describe the analysis of education quality mapping of SMP N 3 Singorojo, Kendal Regency. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data analysis with three steps: data reduction, presenting data, and drawing conclusions. The results showed that: mapping the quality of education at SMP N 3 Singorojo, Kendal Regency is very important to understand where the school is in terms of the quality of education. However, critical analysis shows that the approach used in this mapping still has weaknesses, mainly related to an overly large focus on academic outcomes, neglect of innovations in teaching, as well as the inability to narrow down problems in schools. To improve the overall quality of education, a more holistic mapping is needed that focuses not only on outcomes but also on the process of education and includes non-academic aspects that are important for the overall development of students.